Voices inside the outside: Queer perspectives in hip-hop, RnB and rap - Taylor, Tara "Rei" (Kansas State University, 2024)
This study investigated how queer artists of color within the hip-hop, rap and RnB genres of music expressed narratives of oppression and resiliency, as well as interrogating mirrors of misogynistic messaging from previous research. This research was investigated from Black Feminism, Intersectionality, and a critical Queer perspective. Utilizing a sample of thirteen queer-identifying artists and 205 songs from 1990 to 2022, I examined lyrical content with an Ethnographic Content Analysis framework, and data was also gathered through coding thematic elements. Results indicated that artists were unable to isolate their experiences with racism and queerphobia, rather speaking of them as interconnected. Religiously justified oppression was a predominant portion of these experiences, from a basis of racism and queerphobia alike. Despite this, Resiliency was the most frequently coded thematic element, showing messages of hope and positivity were at the forefront. Additionally, there were concerning trends of depression, self-harm and suicide mentioned explicitly within most albums. This study also found a dearth of misogynistic or anti-femme messaging in comparison to prior research on non-queer artists. Collectively, these findings have implications for future research, as well as policy changes to support the mental health of this vulnerable population.
Keywords: Intersectionality; Queer theory; Hip-Hop Feminism; Content analysis; Black Feminism